(untitled) (Perspectivas em Ciência da Informação, 2023)
The use of Digital Information and Communication Technologies is increasingly present in the daily lives of individuals and institutions, involving tools that facilitate personal, professional and institutional interactions. In today’s technological society, companies use marketing actions to attract customers and position their brands in the market. In this context, the present work aims to verify the technological development of the marketing area between the years 2012 and 2022, analyzing the scientific production and deposits of patent applications. For this purpose, two mappings are carried out, one bibliometric and the other patentometric, with bibliographic and documental procedures. The results indicate that both scientific productions and patents had a publication peak in 2021, possibly driven by the need to formulate actions to circumvent the consequences of social isolation caused by the coronavirus pandemic in 2020. It was also noticed that most of the works focus on the use of technologies in marketing for companies and customers to strengthen their interactions and that the media and social networks are fundamental for this purpose. In addition, most of the returned patents have the classification G06Q 30/02, which covers technologies located in the organization of data for strategic decision making on prices, promotions and other actions aimed at consumers. Finally, it should be noted that this work shows the current stage of the relationship between digital technologies and marketing in the field of research and intellectual property, serving as a starting point for the formulation of new theoretical and/or practical studies.